Micromagnetic Simulation of Transfer Curve in Giant-Magnetoresistive Head - 佘圣贤 韦丹 刘洋 曲炳郡 任天令 刘曦 魏福林 (Chinese physics letters, 2009)
The transfer curve of the giant-magnetoresistive （GMR） magnetic head represents its most important property in applications, and it is calculated by the micromagnetic modeling of the free layer and the pinned layer in the heart of the GMR head. Affections of the bias hard magnetic layer and the anti-ferromagnetic pinning layer are modeled by effective magnetic fields. The simulated transfer curve agrees with experiment quite well, therefore the values of these effective magnetic fields can be determined by the model. A synthetic antiferromagnetic spin valve structure GMR head is also analyzed for comparison.